Exploring Causes of Low English Proficiency Among Burundian Undergraduates Despite Novel Teaching - Déogratias Butoyi; Audace Mbonyingingo; Christopher Joseph Odhiambo (Journal of English Language Teaching and Linguistics, 2026)
English serves as a lingua franca, making high proficiency essential for effective communication across the world. Consequently, numerous studies have been carried out in EFL academic settings to identify and fight causes of low proficiency in English. However, the specific role of the novel in boosting language competence has received little attention or no attention at all, especially at a university in Burundi. Poor proficiency is evident among students in the English Section of Burundi Higher Institute of Education (ENS) and the English Department of the Institute of Applied Pedagogy (IPA, University of Burundi), despite frequent exposure to lectures on the novel in English. This study aimed to investigate how novels are actually used in these institutions, deduce the underlying causes of students' linguistic incompetence, and propose effective solutions to the research problem.  A qualitative research design was employed. A semi-structured, face-to-face interview was conducted with 20 students (half of them from ENS, the other half from IPA) and five literature lecturers (three from ENS and two from IPA) during the academic year 2022-2023. The researcher transcribed textually the recorded voices of both categories of interviewees and analyzed the data using the "Weft QDA" computer software. Findings reveal that novels are taught for their thematic and literary messages, neglecting their potential to promote overall English language skills. These findings answered the research question: “How does the current teaching of the novel at the university in Burundi reflect a focus on English language proficiency vs. literary analysis?” So, the necessity to integrate language skills and the novel at ENS and IPA was expressed. Adopting this approach will significantly improve novel pedagogy and definitely help students overcome the issue of low proficiency in the English language.